Research on the Problems and Countermeasures of the Imbalance of Students’ Subjective Status in the Age of Artificial Intelligence - Li, Wei; Tong, Ju (Asia Pacific Economic and Management Review, 2025)
With the integration of artificial intelligence and curriculum, the direction of school curriculum development has undergone a fundamental change, and the intervention of artificial intelligence in the curriculum is a kind of respect for students’ subject position. However, the immersive experience does not mean the manifestation of students’ self-discipline, and the systematic nature of knowledge is challenged. Students’ self-discipline and motivation should be awakened; at the same time, the systematicity of students’ knowledge should be maintained, and the teacher’s role should be fully utilized to show the power of AI in assisting human beings, so as to highlight the students’ subject position.